1976
DOI: 10.1111/j.1365-2125.1976.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin pharmacokinetics: multicompartmental analysis and its clinical implications.

Abstract: 1 The kinetics of digoxin have been investigated in healthy volunteers using an isotopic tracer technique. 2 A three compartment open kinetic model has been proposed as the simplest model consistent with the plasma, urinary and faecal data obtained. 3 The renal clearance of digoxin (mean ± s.d.) was found to be 119 ± 10 ml/min, which did not differ significantly from the glomerular filtration rate (1 10 ± 14 ml/min). 4 Digoxin extra-renal clearance (mean ± s.d.) was found to be 47 ± 7 ml/min. 5 The model predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 21 publications
(24 reference statements)
3
31
0
Order By: Relevance
“…In this model the 'deep' and 'shallow' compartments both represent tissue spaces and are so called because the rate constant for transfer of drug out of the 'shallow' compartment is an order of magnitude higher than the rate constant for transfer out of the 'deep' compartment. This model has been discussed in more detail in a previous publication (Sumner et al, 1976). Table 5 gives the correlation coefficients between changes in LVET and predicted amounts of digoxin in the 'deep' and 'shallow' compartments separately and together.…”
Section: Compartmental Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model the 'deep' and 'shallow' compartments both represent tissue spaces and are so called because the rate constant for transfer of drug out of the 'shallow' compartment is an order of magnitude higher than the rate constant for transfer out of the 'deep' compartment. This model has been discussed in more detail in a previous publication (Sumner et al, 1976). Table 5 gives the correlation coefficients between changes in LVET and predicted amounts of digoxin in the 'deep' and 'shallow' compartments separately and together.…”
Section: Compartmental Modellingmentioning
confidence: 99%
“…Although the kinetic data can be fitted to a three compartment model (Kramer et al, 1974;Sumner et al, 1976), Table 5 shows that a better correlation is obtained between the change in LVET and the amount of drug in the combined tissue compartments, i.e. the amount of drug in the body less that in the central compartment.…”
Section: Digoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…In man, at least two compartments are required in any pharmacokinetic model to predict adequately the profile of plasma digoxin concentration over a period of several hours after injection (Reuning, Sams & Notari, 1973;Rabkin & Grupp, 1975 Boxenbaum & Reuning, 1974;Koup, Greenblatt, Jusko, Smith & Koch-Weser, 1975;Sumner, Russell & Whiting, 1976). In four human subjects, Sumner et al (1976) described two larger peripheral compartments with marked differences in rate of loss but with similar delays in attainment of maximal digoxin content. In the present study in dogs a slightly modified form of the three-compartment model produced interestingly different conclusions (Figure 2) concerning the time course of digoxin content in the three compartments.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case. Sumner, Russell & Whiting (1976) found that approximately 30% of the elimination of an intravenous digoxin dose is extra-renal in healthy volunteers. This is supported by Cauldwell & Cline's (1975) estimate of biliary excretion.…”
Section: Influence Of Diet On Digoxin Dose Requirementsmentioning
confidence: 99%